Characteristics of lung resistance and elastance associated with tracheal stenosis and intrapulmonary airway narrowing in ex vivo sheep lungs - Yuto Yasuda; Geoffrey N. Maksym; Lu Wang; Pasquale Chitano; Chun Y. Seow (Respiratory Research, 2024)
Abstract Background Understanding the characteristics of pulmonary resistance and elastance in relation to the location of airway narrowing, e.g., tracheal stenosis vs. intrapulmonary airway obstruction, will help us understand lung function characteristics and mechanisms related to different airway diseases. Methods In this study, we used ex vivo sheep lungs as a model to measure lung resistance and elastance across a range of transpulmonary pressures (5–30 cmH2O) and ventilation frequencies (0.125–2 Hz). We established two tracheal stenosis models by inserting plastic tubes into the tracheas, representing mild (71.8% lumen area reduction) and severe (92.1%) obstructions. For intrapulmonary airway obstruction, we induced airway narrowing by challenging the lung with acetylcholine (ACh). Results We found a pattern change in the lung resistance and apparent lung elastance as functions of ventilation frequency that depended on the transpulmonary pressure (or lung volume). At a transpulmonary pressure of 10 cmH2O, lung resistance increased with ventilation frequency in severe tracheal stenosis, whereas in ACh-induced airway narrowing the opposite occurred. Furthermore, apparent lung elastance at 10 cmH2O decreased with increasing ventilation frequency in severe tracheal stenosis whereas in ACh-induced airway narrowing the opposite occurred. Flow-volume analysis revealed that the flow amplitude was much sensitive to ventilation frequency in tracheal stenosis than it was in ACh induced airway constriction. Conclusions Results from this study suggest that lung resistance and apparent elastance measured at 10 cmH2O over the frequency range of 0.125-2 Hz can differentiate tracheal stenosis vs. intrapulmonary airway narrowing in ex vivo sheep lungs.